The Effect of 70o and 85o Electrode Angles on Reverse Welding Techniques On Fusion Depth - Hafni Hafni; Rifqi Rifqi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
Shielded Metal Arc Welding is a liquid welding process (fusion welding) that produces heat from an electric arc between the electrode and the workpiece. The depth of fusion formed is determined by the heat input, the electrode angle and the welding direction. The research was conducted in the Mechanical Engineering laboratory of the Padang Institute of Technology. The test material used is low carbon steel 10 mm thick, 100 mm long and 100 mm wide. Welding is carried out on the surface of the work material as many as 4 welding lines, each of which has a distance of 20 mm. Weld length 100 mm. The specifications of the AWS E 6013 electrode are 3.2 mm in diameter. AC SMAW welding machine with a voltage of 30 Volts. Welding is carried out according to the working drawings, the welding current is 85 Ampere, the electrode angles are 700 and 850, the weld length is 100 mm and the welding direction is reversed (the electrode attracts welding fluid). From the welding, the welding speed is 2.51 mm/s for the 700 electrode angle and 2.48 mm/s for the 850 electrode angle. The heat input for each electrode angle is 1024.09 J/mm. at the 700 electrode angle has a penetration presentation of 10.85%, 1.14% greater than the 850 electrode angle. This shows that the electrode angle affects the penetration depth and weld width.